2003
DOI: 10.1034/j.1600-6143.2003.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Theory of Transplantation

Abstract: According to the humoral theory of transplantation, antibodies cause allograft rejection. Publications are cited showing that antibodies: (1) cause hyperacute kidney rejection, (2) lead to C4d deposits associated with early kidney graft failures, (3) are a good indicator of presensitization leading to early acute rejections, (4) were present in 96% of 826 patients who rejected a kidney graft, (5) are associated with chronic rejection in 33 studies of kidney, heart, lung and liver grafts, and (6) in three studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
391
1
19

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(423 citation statements)
references
References 120 publications
12
391
1
19
Order By: Relevance
“…The important role of these anti-HLA AlloAb in mediating rejection had been emphasized first by Terasaki. 1 The antibodies found in the peripheral circulation were not necessarily donor-specific, and their association with failure was consistent with a causality hypothesis. 2 Several studies observed that patients who had rejected transplants displayed anti-HLA antibodies more frequently than those with functioning grafts.…”
supporting
confidence: 60%
“…The important role of these anti-HLA AlloAb in mediating rejection had been emphasized first by Terasaki. 1 The antibodies found in the peripheral circulation were not necessarily donor-specific, and their association with failure was consistent with a causality hypothesis. 2 Several studies observed that patients who had rejected transplants displayed anti-HLA antibodies more frequently than those with functioning grafts.…”
supporting
confidence: 60%
“…Preformed anti-donor class II antibodies increase the risk of transplant failure [1][2][3][4][5][6][7][8][9] and the post-transplant development of anti-class II antibodies is associated with a higher incidence of acute and chronic rejection [10][11][12][13][14][15][16][17][18][19] Current class II matching strategies for kidney transplantation consider only the HLA-DR antigens controlled by the DRB1 locus but mismatching for HLA-DQ and HLA-DP may also lead to lower graft survival rates [20][21][22][23][24][25]. Newer serum screening methods such as ELISA, Flow Cytometry and Luminex have greatly enhanced the detection of anti-HLA-DQ and HLA-DP antibodies and their association with transplant rejection [2,7,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…1 At present the exact mechanism of this chronic allograft rejection is not clear, but it has become evident that both innate and adaptive immune responses play an important role in the onset and pathogenesis of BOS. [2][3][4][5] Natural killer (NK) cells are one of the main cellular components of the innate immune system and are important in the lysis of virally infected cells and tumors. The NK cells express a multitude of intracellular and extracellular proteins in order to recognize and eliminate target cells.…”
mentioning
confidence: 99%